2013
DOI: 10.1179/1743676113y.0000000078
|View full text |Cite
|
Sign up to set email alerts
|

Development of ceramic based on steel slag with different magnesium content

Abstract: The steel slag based ceramics (SSBC) with different contents of magnesium ions were prepared by conventional sintering process. The variations of linear shrinkage, water absorption, bulk density and apparent porosity of the samples fired at different temperatures from 1130 to 1210uC were measured. The phase formation and microstructure of final ceramics were observed by Xray diffraction (XRD) and scanning electron microscopy (SEM). The results indicate that increasing magnesium ions content in SSBC does not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…The authors also reported that increasing EAF slag to 50 wt.% would produce ceramic tiles that were too brittle. Similar research works were conducted by [20][21][22]29,[102][103][104][105][106][107][108][109][110], who mutually agreed that the optimal amount of EAF slag added was in the range of 30-50 wt.%. Meanwhile, the optimal firing temperature for the ceramic product incorporated with EAF slag was in the range of 1050 • C-1250 • C. Most of these studies were able to prove that the ceramic product incorporated with EAF slag had physical and mechanical properties comparable with commercially available products.…”
Section: Raw Materials For Ceramic Productssupporting
confidence: 56%
“…The authors also reported that increasing EAF slag to 50 wt.% would produce ceramic tiles that were too brittle. Similar research works were conducted by [20][21][22]29,[102][103][104][105][106][107][108][109][110], who mutually agreed that the optimal amount of EAF slag added was in the range of 30-50 wt.%. Meanwhile, the optimal firing temperature for the ceramic product incorporated with EAF slag was in the range of 1050 • C-1250 • C. Most of these studies were able to prove that the ceramic product incorporated with EAF slag had physical and mechanical properties comparable with commercially available products.…”
Section: Raw Materials For Ceramic Productssupporting
confidence: 56%
“…Al 2 O 3 is first involved in the formation of anorthite, followed by the disappearance of the anorthite phase into the liquid phase, and finally, solid solution into the pyroxene phase. Ai et al [22] prepared steel slag ceramics with different MgO contents, and studied the influence of MgO on sintering temperature and crystal phase.…”
Section: Introductionmentioning
confidence: 99%
“…Bauxite is widely distributed in nature as a natural alumina mineral. The high-grade bauxite contains alumina up to 85% or more, and the other components such as SiO 2 , TiO 2, and CaO can be used as natural additives for alumina sintering, that can effectively reduce the sintering temperature and porosity and improve the properties of the materials [21]. At present, bauxite is only used as a raw material for extracting alumina or preparing refractories [22,23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%